PENGARUH KEBIJAKAN UTANG DAN KEBIJAKAN DEVIDEN TERHADAP NILAI PERUSAHAAN SUBSEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2020 - Waluyo Waluyo; Siti Rohayati (BALANCING: Accountancy Journal, 2022)
The data collection technique use documentation techniques with secondary data and the analytical method used is a correlational analysis using SPSS 25.0. There are 8 pharmaceutical sub-sector companies listed on the IDX which are analyzed. Data on Debt policy, Dividend policy, and Company Value are taken from the 2017-2020 financial statements. This study also uses the classic assumption test and hypothesis testing to determine the effect of Debt Policy, Dividend Policy, and Firm Value.